VARIASI TINGKAT KEMATIAN BAYI DAN HARAPAN HIDUP DI INDONESIA MENURUT PROPINSI: HASIL SENSUS PENDUDUK 1990 - Kasto Kasto (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1992)
This study tries to investigate the infant mortality rate and life expectancy based on the 1990 Population Census, and to observe its variations among provinces that take place in the urban as well as in the rural areas of Indonesia. As a whole, the estimate of infant mortality rate and the expectation of life based on the 1990 Population Census is 69 per one thousand life births and 60 years for both urban and rural areas. The variation in the rural areas is larger than in the urban regions.During the period from 1980 to 1990 the infant mortality rate in Indonesia decreased by 4.29 percent annually. If this rate continued to increase till the end of 2000, the infant mortality rate by this time would be 45 per one thousand life births, whereas the expectation of life at birth would become 68 years.Many determinants of infant mortality rates should be taken into account to reduce the figures, particularly the coverage and the quality of the public health service which directly influences the child survival, as well as other determinants which indirectly,yet simultaneously, influence it.